Filosofis Ketuhanan dalam Konsep Islam Menuju ketauhidan - Wahyudin Wahyudin (Pascasarjana IAIN Metro, 2017)
God does not require the properties and values ​​in addition to his perfection but creatures need, hunger and depend on the form of terrain, terrain divinity and divinity to ride their Existence. The terrain is not intended space. If a creature receives Emission or God creature would be destroyed and perish. Divinity into solid closed protects Existence of creatures and save them. Existence is no closed is to protect God's creation barrier Existence by divinity is stable, true and eternal entity. Various views that want to change the core of the program (monotheism) divinity in Islam, both of which come from outside of Islam even among Islamic all in stagnation. Ness program agreed core issues, which distinguishes the way, the practice of worship, interpretation leads to divinity, giving rise to a prolonged polemics.